Controlled preparation and properties of acrylic acid epoxy‐acrylate composite emulsion for self‐crosslinking coatings. Issue 1 (23rd July 2021) - Zhang, Kai; Li, Li; Chen, Xifang; Lu, Chenghang; Ran, Jingwen
Abstract: A stable epoxy‐acrylate composite latex was successfully prepared through emulsion polymerization of modified epoxy acrylic (EPAC) oligomer with acrylate monomer. The EPAC oligomer was obtained using active acrylic acid (AA) to react with epoxy resin. And by regulating the reaction degree of the active hydrogen of AA and epoxide group, there is the acquisition of terminal double bond that gives EPAC reactivity, together with the partial retention of the epoxide group that enables self‐crosslinking during film formation. The structural conformation of the oligomer was ascertained by Fourier transform infrared (FTIR) spectroscopy. The factors influencing the stability of the epoxy‐acrylate composite latex were investigated. The epoxy‐acrylate composite latex was the most stable when methyl acrylic acid was 1.5 wt% and modified EPAC oligomer was 15 wt% of the total monomer weight. The morphology and property of the composite latex films were characterized by scanning electron microscopy, transmission electron microscopy (TEM), and temperature‐modulated differential scanning calorimetry (TOPEM‐DSC). The results confirm that there is successful emulsion copolymerization between modified EPAC oligomer and acrylate monomer. TEM show that the particles of epoxy‐acrylate composite have a core‐shell structure, and there is no free epoxy resin. The FTIR and TOPEM‐DSC results reveal that the copolymer emulsion possesses self‐crosslinking ability. During film formation, self‐crosslinking reaction occurs between epoxide groups with carboxyl groups, giving exothermal phenomena. The thermal stability as well as the corrosion resistance of the films was analyzed. The results show outstanding thermal stability as well as corrosion resistance attributable to the crosslinking reticulation structure. It is envisaged that the epoxy‐acrylate composite latex has great potential in the development of high‐performance aqueous coatings. Abstract :